O quotidiano na construção do imaginário e da identidade - Almeida, Paulo Oliveira Freire (2015)
Usually the artist doesn’t create useful objects. In fact, utility and functionality are design problems. However, the artists are interested in the depiction and status of objects and urban equipment with the stories and meanings associated with those artifacts. In this paper, it is argued that art has recovered to identity, a landscape devoid of identity qualities: the suburbs, the wasteland, the “non-place” (Augé 1994). In the context of Everyday Aesthetics there is a claim of ‘ prosaic or colloquial’ forms as opposed to ‘poetic’ ones (Mandoki). As Haapala wrote, art and aesthetics are related to the strange and unique space, without attention to the everyday functional objects. So, houses, streets, urban equipment are depleted in its functional roles. But the aesthetics of everyday life looks for fulfilment and identity in familiar places. In the fine arts of painting and drawing there is a return to the depiction of daily-domestic landscape and domestic interior where the presence of the prosaic and ordinary furniture, common objects, equipment, signs and clothes, creates a paradox. On the one hand, ordinary comodities suggest the destruction of local identity and traditional landscape and memory. On the other hand establish new visual references not yet assimilated. This paper cross the theory about the aesthetics of the everyday life of Arto Haapala and Katya Mandoki with three contemporary artists: George Shaw (1966), Matthias Weischer (1973) and Simon Stalenhag (1984), in which realism is underlined by the identity of prosaic and everyday elements of architecture and design, opening room for dream, the absurdity and science fiction. The solution for this apparent contradiction between reality and reverie lies in reference to quotidian and prosaic, filtered by the concepts of anachronism, melancholy and desertion. In these paintings the design of the objects and equipment is vital in the statement of the identity of places and authors through a process of time encapsulation.